2019
DOI: 10.1111/are.14020
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofArthrospirasupplementation onOreochromis niloticusgut microbiota and flesh quality

Abstract: Supplementing fish feed with Arthrospira platensis has several beneficial effects, such as improved growth, survival and feed conversion, but little is known about how it affects gut microbiota or flesh quality. In this trial, feed with 3% A. platensis was given to Oreochromis niloticus (SPR, spirulina supplemented) over a period of 50 days and their gut microbiota and flesh quality were compared with controls (CTRs, no supplementation). Average daily growth was higher in SPR fish (p < 0.05). Regarding microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Ingestion has an important effect on the intestinal microbes and their functions in tilapia [52]. And, the microbiota can also affect behaviors [53], including feeding behavior, digestive/ absorptive processes (e.g., by modulating intestinal motility and the intestinal barrier) [54], metabolism, as well as the immune response, with repercussions on the energy homeostasis, growth status [55] and health of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion has an important effect on the intestinal microbes and their functions in tilapia [52]. And, the microbiota can also affect behaviors [53], including feeding behavior, digestive/ absorptive processes (e.g., by modulating intestinal motility and the intestinal barrier) [54], metabolism, as well as the immune response, with repercussions on the energy homeostasis, growth status [55] and health of the host.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the Spirulina biomass, the Arthrospira platensis BIO1 strain, kindly supplied by Biodesma S.L., was used. A. platensis was grown in plastic bioreactors in a greenhouse at the Universidad Politécnica de Madrid (40.446353 N-3.738341 E), as previously described [ 24 , 25 ]. Briefly, A. platensis was harvested when the culture reached approximately 1 g/L of dry weight.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary additives of microalgae Spirulina and Schizochytrium, used as replacements for FM, FO or plant oil, significantly improved fish growth and maintained fillet quality and displayed the potential of using these microalgae as sustainable alternatives in aquafeeds to enhance fish growth and the quality of fillets while reducing reliance on traditional protein sources like FM and FO [133]. Dietary supplementation of Sargassum ilicifolium (10%) during an eight-week feeding trial with great sturgeon revealed several positive effects, including enhanced growth performance, hematological parameters (red blood cells (RBCs), white blood cells (WBCs), and hemoglobin levels), immune responses (respiratory bursts, complementary activities, and immunoglobulin M, lysozyme, and serum total protein levels), and defense against Y. ruckeri and highlight the potential of S. ilicifolium as a valuable dietary supplement for improving the health and growth performance of great sturgeon [134]. Dietary inclusion of macroalgae Gracilaria vermiculophylla at a level of 5% in a 91-day feeding trial improved the growth performance of rainbow trout, enhanced the innate immune response, and resulted in the highest peroxidase, complement, and lysozyme activity [135].…”
Section: Growth Promotersmentioning
confidence: 99%